2022
DOI: 10.1038/s41598-022-10954-x
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at sex pheromone autodetection in the Oriental fruit moth

Abstract: Female moths emit sex pheromone to attracts males, and although they are not attracted to their own sex pheromone, they appear to detect it as it affects their behavior. In order to elucidate the mechanism of pheromone “autodetection” we compared responses of olfactory receptor neurons (ORNs) of male and female Grapholita molesta, a species with reported pheromone autodetection. Two concentrations of the major (Z8-12:Ac) and minor (E8-12:Ac) sex pheromone components, a plant-volatile blend containing methyl sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Amounts of impurities in test stimuli and unspecific responses associated with high dosage may also obscure true ligand-receptor relationships [62][63][64]. Research on G. molesta concluded that females did not respond to female-produced sex pheromones and furthermore suggest that female autodetection observed in other species may be largely artefacts of high dosages or impurities in stimuli [56]. However, in this study most of the odorants selected had relatively similar size, vapor pressures and high purity.…”
Section: Sensitivity To Female Sex Pheromonesmentioning
confidence: 68%
See 1 more Smart Citation
“…Amounts of impurities in test stimuli and unspecific responses associated with high dosage may also obscure true ligand-receptor relationships [62][63][64]. Research on G. molesta concluded that females did not respond to female-produced sex pheromones and furthermore suggest that female autodetection observed in other species may be largely artefacts of high dosages or impurities in stimuli [56]. However, in this study most of the odorants selected had relatively similar size, vapor pressures and high purity.…”
Section: Sensitivity To Female Sex Pheromonesmentioning
confidence: 68%
“…In the tortricid moth, C. pomonella, cross-adaption studies of the codlemone type receptor showed a reduced response to all codlemone isomers and E8, E10-12:Ac a short time (5 s) after stimulation with E8,E10-12:OH at a high dose of 10 µg and less adaptation when stimulated with the same dose of E8,Z10-12:OH [55]. Another study on Heliothis subflexa Guenée (Lepidoptera: Noctuidae) and Heliothis virescens F. (Lepidoptera: Noctuidae) to components of their sex pheromones confirmed the presence of two ORNs usually having different spike sizes and tuned to different components ((Z)-11-16Ac and (Z)-11-16:OH) [56]. However, the same study showed that in H. subflexa, (Z)-11-16Ac tuned neuron also elicited responses to (Z)-9-14Ald with nearly equivalent sensitivity [57].…”
Section: Sensitivity To Female Sex Pheromonesmentioning
confidence: 88%
“…This may affect their longevity and reproductive potential as repeated calling is costly (Harari et al 2011). Alternatively, since females are relatively anosmic to their own sex pheromone, especially towards the minor pheromone components (Vitagliano et al 2005;Pérez-Aparicio et al 2019), the observed response to mating disruption concentrations of sex pheromone may not be due to a pheromone autodetection sensu stricto (Holdcraft et al 2016) but to the consequence of misleading odour stimulation (Pérez-Aparicio et al 2022). In either case, the implications of changes in female behaviour under mating disruption deserve further study (Pérez-Aparicio et al 2022).…”
Section: Sexual Behaviourmentioning
confidence: 99%